Hegel in the Light of Fichte’s Metacritical Project: The Absolute Idea and the Worldly Embodiment of Thought (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: Fichte, as is well known, was a self-declared Kantian; but, at the same time, he paved the way for a renewed and truly original project. If Kant sought for the conditions of the possibility of objectivity, Fichte went even further, asking for the conditions of possibility of this very Kantian program. This is what we may call Fichte’s ‘metacritical’ project. Whereas Kant thought of subjectivity as a mere object of our knowledge, and thereby, as divorced from the real, worldly subjects who carry out this inquiry itself, Fichte’s metacriticism raised the demand for the unity of both pure and embodied thinking. If the subject is to be ‘self’-thinking, it cannot be ‘our’ object only, but rather the ‘subject-object’ unity. Hegel’s philosophy is to be thought of in this very metacritical framework. His absolute Idea, indeed, as the completion of his own System, is intended to be the ‘self’-thinking Idea, and in this way to comprise within itself both the purely logical and the real, empirical subject.